Attitudes of students from south-east and east Asian countries to slaughter and transport of livestock - Ling, R. Z.; I., Zulkifli; Lampang, P. N.; Nhiem, D. V.; Wang, Y. G.; Philips, C. J. C. (Universities Federation for Animal Welfare, 2016)
Attitudes to animals have been extensively studied for people in developed countries, but not for those in developing countries. The attitudes of prospective stakeholders in the livestock sectors in south-east and east Asia toward transport and slaughter were examined by surveying university students studying veterinary medicine and animal science in Malaysia, Thailand, China and Vietnam, with a total of 739 students taking part. Students had greater acceptability of transport than slaughter issues for livestock, and female students found most transport and slaughter issues of greater concern than male students. Veterinary students were more accepting of several issues than animal science students, in particular killing animals that were injured or ill. Religion had a major effect on attitudes. Muslim students found using animals that died naturally for products least acceptable. Compared to them, Hindu students were less accepting of killing injured or ill animals and Buddhist students less accepting of euthanasing healthy pets. Students with more experience of pets were less accepting of both transport and slaughter issues. It is concluded that concern was exhibited by future stakeholders in the SE and E Asian livestock industries for slaughter and, to a lesser extent, transport issues, although attitudes were influenced by their religion, gender and experience of pet-keeping.